2023
DOI: 10.1021/acs.langmuir.3c01429
|View full text |Cite
|
Sign up to set email alerts
|

Selective Chiral Recognition between Amino Acids and Growing Gypsum Crystals

Jing Gao,
Haibin Li,
Zhiheng Sun
et al.

Abstract: In nature, selective chiral interactions between biomolecules and minerals provide insight into the mysterious origin of homochirality. Here, we show growing gypsum crystals in a nonequilibrium state can recognize chiral enantiomers of amino acids. The chiral selection for amino acids with different functional groups by growing minerals are distinct. For 11 amino acids, the D-isomer slows dynamic gypsum growth more than the L-isomer, whereas for another 7 amino acids, the opposite was observed. These differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Chirality (handedness) is universal in nature, even in the cosmos across a very large-scale range and plays an important role in the scientific community and the human body. Chiral molecules have two enantiomeric forms that usually exhibit the same chemical properties but have different biological properties because of the inherent chirality of biological systems. Many essential biochemicals, such as natural amino acids (except glycine) and simple sugars, are chiral and exist in only one isomeric (mirror) form. Other than organic molecule-based systems, chiral inorganic nanostructures have attracted extensive interest recently. Chiral surfaces, clusters, and low-dimensional nanomaterials have been obtained via various strategies and their chiral features have been studied using powerful techniques. , Previous studies proved that the enantiomers of chiral molecules exhibit similar physical or chemical properties but may exhibit different physiological functions and even generate opposite physiological toxicity. Therefore, reliable and effective methods for chiral discrimination and quantification of enantiomers are very helpful for understanding the chiral asymmetric interactions on their physicochemical properties, especially in interfacial science applications. , …”
Section: Introductionmentioning
confidence: 99%
“…Chirality (handedness) is universal in nature, even in the cosmos across a very large-scale range and plays an important role in the scientific community and the human body. Chiral molecules have two enantiomeric forms that usually exhibit the same chemical properties but have different biological properties because of the inherent chirality of biological systems. Many essential biochemicals, such as natural amino acids (except glycine) and simple sugars, are chiral and exist in only one isomeric (mirror) form. Other than organic molecule-based systems, chiral inorganic nanostructures have attracted extensive interest recently. Chiral surfaces, clusters, and low-dimensional nanomaterials have been obtained via various strategies and their chiral features have been studied using powerful techniques. , Previous studies proved that the enantiomers of chiral molecules exhibit similar physical or chemical properties but may exhibit different physiological functions and even generate opposite physiological toxicity. Therefore, reliable and effective methods for chiral discrimination and quantification of enantiomers are very helpful for understanding the chiral asymmetric interactions on their physicochemical properties, especially in interfacial science applications. , …”
Section: Introductionmentioning
confidence: 99%
“…For instance, dynamic growth steps of brushite and calcite have been shown to selectively bind with chiral isomers of amino acids, leading to the formation of biominerals with distinct chiral characteristics. In our previous work, we found that chiral selections of amino acids with different functional groups on dynamic growing gypsum steps are distinct. These differences in chiral recognition are attributed to the different stereochemical matching between chiral amino acids and the dynamic steps of growing gypsum . However, how the side chains of chiral amino acids regulate the stereochemical matching between amino acids and crystals is still unknown.…”
Section: Introductionmentioning
confidence: 99%